2003
DOI: 10.5012/bkcs.2003.24.9.1245
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Amine Nature on Rates and Mechanism: Pyridinolyses of 4-Nitrophenyl Benzoate

Abstract: Pseudo-first-order rate constants (kobs) have been measured spectrophotometrically for the reactions of 4nitrophenyl benzoate with a series of pyridines in H 2 O containing 20 mol % DMSO. The plots of kobs vs pyridine concentration are linear up to ca. 0.1 M pyridines, indicating that the effect of self-association of pyridines with their conjugate acids are insignificant in this concentration range. The Brønsted-type plot has been obtained to be linear with a β nuc value 1.11, suggesting that the pyridinolyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…The pyridinolysis of 4-nitrophenyl benzoate in water shows a linear Brønsted-type plot with slope 1.1, consistent with a stepwise mechanism where breakdown of the intermediate T ± is rate-determining . This result is in agreement with the curved Brønsted plot, with p = 9.7, obtained for the pyridinolysis of thiolbenzoate 1 in aqueous ethanol (this work), on the following grounds.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The pyridinolysis of 4-nitrophenyl benzoate in water shows a linear Brønsted-type plot with slope 1.1, consistent with a stepwise mechanism where breakdown of the intermediate T ± is rate-determining . This result is in agreement with the curved Brønsted plot, with p = 9.7, obtained for the pyridinolysis of thiolbenzoate 1 in aqueous ethanol (this work), on the following grounds.…”
Section: Resultssupporting
confidence: 89%
“…Even the amidium cations derived from very basic pyridines are rapidly hydrolyzed. 1-Benzoyl-4-(dimethylamino)pyridinium could not be detected in the reaction of this pyridine with 4-nitrophenyl benzoate in water . Nevertheless, the acetylpyridinium derivatives are more stable toward hydrolysis, as indicated by the fact that 1-acetyl-4-(dimethylamino)pyridinium has been observed spectrophotometrically in the reaction of this pyridine with acetic anhydride and 2,4-dinitrophenyl thiolacetate in aqueous solution .…”
Section: Methodsmentioning
confidence: 82%
“… a The p K a data in 80 mol % H 2 O/20 mol % DMSO were taken from ref . b Determined in this study by using the method shown in ref . …”
Section: Resultsmentioning
confidence: 99%
“…Ester hydrolysis is an important type of reaction that has received a great deal of attention in both organic chemistry and biochemistry, and it has been subjected to many investigations. …”
Section: Introductionmentioning
confidence: 99%